Numerical optimization of multistage packing pressure profile in plastic injection molding and experimental validation. (25th May 2022) - Kitayama, Satoshi; Matsubayashi, Akihiro; Takano, Masahiro; Yamazaki, Yusuke; Kubo, Yoshikazu; Aiba, Shuji
Abstract: Plastic injection molding (PIM) is a crucial processing technology for producing lightweight products. Process parameters such as melt temperature, packing pressure, and cooling time directly affect not only the product quality but also the productivity, and they are conventionally adjusted by the trial‐and‐error method. A constant packing pressure is conventionally used, but the multistage packing pressure profile recently attracts attention. However, the packing pressure profile is unknown in advance, and it is difficult to determine it through the trial‐and‐error method. In this paper, the multistage packing pressure profile as well as other process parameters so as to minimize the warpage and cycle time are determined by using computational intelligence and design optimization. It is found from the numerical result that 27% warpage and 50% cycle time reduction can be achieved, compared with ones using reference process parameters. In addition, it is clarified that clamping force can be reduced. This indicates that PIM using the optimal multi‐stage packing pressure profile can produce plastic product with small clamping force that makes the tool life long. Finally, the experiment using PIM machine equipped with servo controller (MS100, Sodick) is carried out to examine the effectiveness of the multistage packing pressure profile.